Comparison of perioperative analgesia using the infiltration of the surgical site with ropivacaine alone and in combination with meloxicam in cats undergoing ovariohysterectomy - De Ol Carapeba, Gabriel; Nicácio, Isabela P. G. A.; Stelle, Ana Beatriz F.; Bruno, Tatiane S.; Nicácio, Gabriel M.; Costa Júnior, José S.; Giuffrida, Rogerio; Teixeira Neto, Francisco J. [UNESP]; Cassu, Renata N. (Springer Nature, 2020)
Background: Infiltration of the surgical site with local anesthetics combined with nonsteroidal anti-inflammatory drugs may play an important role in improving perioperative pain control. This prospective, randomized, blinded, controlled clinical trial aimed to evaluate intraoperative isoflurane requirements, postoperative analgesia, and adverse events of infiltration of the surgical site with ropivacaine alone and combined with meloxicam in cats undergoing ovariohysterectomy. Forty-five cats premedicated with acepromazine/meperidine and anesthetized with propofol/isoflurane were randomly distributed into three treatments (n = 15 per group): Physiological saline (group S), ropivacaine alone (1 mg/kg, group R) or combined with meloxicam (0.2 mg/kg, group RM) infiltrated at the surgical site (incision line, ovarian pedicles and uterus). End-tidal isoflurane concentration (FE'ISO), recorded at specific time points during surgery, was adjusted to inhibit autonomic responses to surgical stimulation. Pain was assessed using an Interactive Visual Analog Scale (IVAS), UNESP-Botucatu Multidimensional Composite Pain Scale (MCPS), and mechanical nociceptive thresholds (MNT) up to 24 h post-extubation. Rescue analgesia was provided with intramuscular morphine (0.1 mg/kg) when MCPS was ≥6. Results: Area under the curve (AUC) of FE'ISO was significantly lower (P < 0.0001) in the RM (17.8 ± 3.1) compared to S (23.1 ± 2.2) and R groups (22.8 ± 1.1). Hypertension (systolic arterial pressure > 160 mmHg) coinciding with surgical manipulation was observed only in cats treated with S and R (4/15 cats, P = 0.08). The number of cats receiving rescue analgesia (4 cats in the S group and 1 cat in the R and RM groups) did not differ among groups (P = 0.17). The AUC of IVAS, MCPS and MNT did not differ among groups (P = 0.56, 0.64, and 0.18, respectively). Significantly lower IVAS pain scores were recorded at 1 h in the RM compared to the R and S groups (P = 0.021-0.018). There were no significant adverse effects during the study period. Conclusions: Local infiltration with RM decreased intraoperative isoflurane requirements and resulted in some evidence of improved analgesia during the early postoperative period. Neither R nor RM infiltration appeared to result in long term analgesia in cats undergoing ovariohysterectomy.
Keywords: Analgesia; Feline; Infiltration; Local anesthetic; Non-steroidal anti-inflammatory drug